Biology of Pentalonia nigronervosa and Its Efficiency as a Vector of Banana Bunchy Top Virus After Being Bred in Rat Taro (Typhonium flagelliforme) - Yunanda Audri Balqis; Bambang Gunawan; Suparman SHK (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2023)
P. nigronervosa is an insect that acts as a vector of the Banana Bunchy Top Virus causing the affected banana  to become stunted and even fruitless. This study aimed to find out the biology of P. nigronervosa in rat taro as well as its  ability or efficiency in the transmission of BBTV disease in bananas after being treated. The study was experimenta, trying to find out the efficiency of BBTV transmission by P. nigronervosa after being transmitted to the plant of rat taro (T. flagelliforme) with  the variables of observation and  the taking of biological  data  of Pentalonia nigronervosa  in the rat taro plant, Observation of the development of BBTV disease in banana plants inoculated from the first symptoms until the typical phenomenon of bunchy top was formed. Biology of P.  nigronervosa in  rat taro. Each stage of the four color instars and The size of the nymph of P. nigronervosa changed. When entering the first brownish-white instar with a length of 0.61 to 0.69 mm, in the 2nd instar it was light brown with a length of 0.71 to 0.83 mm, then in the 3rd instar it was reddish brown with an average length of 0.87 mm, and in the 4th instar  it was blackish brown with an average body length of 1.31 mm. The imago color was still blackish brown, and in this phase it usually had wings, but in the treatment of the imago rat taro plant, it had no wings, and the average body length was 1.43 mm. In the field tests, the rat taro plants could not inhibit the spread of BBTV disease but could be an alternative host for P. nigronervosa ticks.